Frequency of Glucose 6 Phosphate Dehydrogenase Deficiency in Neonates Presenting with Jaundice - Mushtaque Ali Shah, Bushra, Muhammad Touseef, Shahjahan Fazlani, Abdul Hameed Radhan, Nazimuddin, Muhammad Nadeem Chohan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Frequency of Glucose – 6- Phosphate Dehydrogenase deficiency in neonates presenting with jaundice Study design: A cross-sectional study Place and Duration: Pediatric department, civil hospital Karachi from January to June 2019 Methodology: The study included all infants who were hospitalized in the neonatology unit with jaundice. At the beginning of the trial, the parents of each neonate gave their assent after being assured that there would be no monitoring burden placed on the parents for the examinations. When entering the hospital, the researcher himself completed a predesigned proforma that asked for specific details about the patient's age, sex, ethnicity, jaundice onset age, consanguinity, and family history of G6PD deficiency. Investigations on newborns included measuring serum bilirubin and looking for signs of G6PD deficiency. (Estimation of G6PD enzymes). Sigma Diagnostic G6PD Reagent was used to estimate the G6PD enzymes for the qualitative, visual, and calorimetric assessment of G6PD deficit in red blood cells. When the sample's deep blue colour changes Results: 174 infants with jaundice in total were included during the study period. Participants in the study had an average age of 16.12 +/- 7.2 days. 95 (54.6%) of the 174 study participants were men, and the male-to-female ratio was 1.2:1. It started at an average age of 8.83.8 days. 79 (45.5%) out of a total of 117 (67.2%) participants are Pathans by consanguineous marriage. 23 (13.2%) of the 174 subjects were G6PD deficient. According to a stratified analysis, out of 23 G6PD-deficient newborns, 11 (47.8%) were between 1 and 11 days old, 19 (82.6%) were between 0 and 6 days old, and 14 (60.8%) had blood bilirubin levels below 15 mg/dl. Conclusion: It was concluded that G6PD is a common cause of neonatal jaundice in our setup. Keywords: Neonates, Jaundice, G6PD deficiency